ANALYSIS OF ADVANCED MATHEMATICS BOOKS BASED ON PANCASILA PROFILE ON CRITICAL REASONING DIMENSIONS - Mahtum, Rohikim; Pribadi, Maharani Hayuning Pangastuti; Magfiroh, Aula Zahrotin; Sunardi, Sunardi; Lestari, Nurcholif Diah Sri (Nurul Jadid University, 2023)
Pancasila students embody Indonesian students who have competence and behave according to Pancasila values. One of the elements of the Pancasila profile is critical reasoning which is contained in advanced mathematics books and will be a provision for Indonesian students, especially phase E at SMA/SMK levels in an effort to develop themselves and face challenges in the 21st century. The purpose of this research is to analyze student books in accordance with aspects of the values of the Pancasila Student Profile which focus on elements of critical reasoning and provide recommendations as material for consideration in improving student books. This type of research is qualitative with a descriptive approach. The results obtained are books that are relevant and encourage students to reason critically by presenting various problem solutions, and there is a special column entitled